1992
DOI: 10.1115/1.2905924
|View full text |Cite
|
Sign up to set email alerts
|

The Component Equations of Energy and Exergy

Abstract: Energy conversion processes inherently have associated irreversibility. A better understanding of energy conversion will motivate intuition to create new energy-conversion and energy-utilization technology. In the present article, such understanding is further enhanced by decomposing the equations of energy and exergy (availability, available energy, useful energy) to reveal the reversible and irreversible parts of energy transformations. New definitions of thermal, strain, chemical, mechanical and thermochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…It is observed that PFBC is by far responsible than any other components of the plant for exergy destruction. Exergy loss may arise from different sources like heat transfer with finite temperature difference, internal dissipative effects, mixing of streams, chemical reactions or interactions with the environment etc (Dunbar et al, 1992;Facchini et al, 2000). In PFBC, exergy loss occurs due to all of these factors and hence it is responsible for maximum loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that PFBC is by far responsible than any other components of the plant for exergy destruction. Exergy loss may arise from different sources like heat transfer with finite temperature difference, internal dissipative effects, mixing of streams, chemical reactions or interactions with the environment etc (Dunbar et al, 1992;Facchini et al, 2000). In PFBC, exergy loss occurs due to all of these factors and hence it is responsible for maximum loss.…”
Section: Resultsmentioning
confidence: 99%
“…In part I, the exergy analysis of air-cooled Brayton cycle and in part II, that of two-pressure steam bottoming cycles were discussed. For a better understanding of energy conversion processes and their inherent associated irreversibilities, Dunbar et al (1992) discussed the component equations of energy and exergy. Graphical exergy analysis of gas turbine cycle with saturated air (GTSA) was presented by Jin and Ishida (1994).…”
Section: Introductionmentioning
confidence: 99%
“…Dunber [1] presented the general theory of thermodynamic exergy and its application to energy systems. Soma [2] presented design and analysis theory of exergy combined thermodynamic energy transfer with its transformation and made some application analysis.…”
Section: Introductionmentioning
confidence: 99%
“…where the suffixes indicate the usual denomination of the various terms: Physical, chemical, kinetic, potential exergy [73]. If other forms of energy fluxes are involved (magnetic, nuclear, etc.…”
Section: The Concept Of Exergymentioning
confidence: 99%